2017
DOI: 10.3892/br.2017.1005
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan is effective in treating patients with refractory ascites due to cirrhosis

Abstract: Abstract. The treatment of refractory ascites due to cirrhosis is a clinical challenge for hepatologists. Tolvaptan, a novel aquaporin modulator, was made available in Japan in 2013 for the treatment of patients with refractory ascites due to cirrhosis. Despite the potential of this drug, few reports are available regarding its clinical use. The aim of the present study was to clarify the efficacy of tolvaptan in patients with refractory ascites due to cirrhosis and to review the clinical outcomes of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…There was no report that tolvaptan was associated with longer survival time in patients with heart failure [19][20]. On the other hand, some reports showed that tolvaptan responders were associated with longer survival time in cirrhotic patients [8,[21][22][23]. Tahara et al [23] reported that tolvaptan response was associated with longer survival time, and renal function (an eGFR ≥55 mL/min) was one of the significant predictors of response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no report that tolvaptan was associated with longer survival time in patients with heart failure [19][20]. On the other hand, some reports showed that tolvaptan responders were associated with longer survival time in cirrhotic patients [8,[21][22][23]. Tahara et al [23] reported that tolvaptan response was associated with longer survival time, and renal function (an eGFR ≥55 mL/min) was one of the significant predictors of response.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, some reports showed that tolvaptan responders were associated with longer survival time in cirrhotic patients [8,[21][22][23]. Tahara et al [23] reported that tolvaptan response was associated with longer survival time, and renal function (an eGFR ≥55 mL/min) was one of the significant predictors of response. Our results were consistent with their report in these points.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, loop diuretics and spironolactone become less effective as liver cirrhosis advances and increasing doses are needed to be administered in order to achieve adequate diuretic response. 45 No predictive value was proposed by the existing evidence for baseline urine osmolality or 24-h urine sodium excretion. As a result, it can be assumed that high diuretic doses may diminish the effectiveness of tolvaptan by reducing renal perfusion and down-regulating the expression of aquaporin-2.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, hepatitis C was linked to tolvaptan response, although the exact etiology of this observation remains unclear; it can be assumed that in contrast to hepatitis C-infected patients, alcohol-related cirrhosis is associated with higher rates of delays in treatment initiation and with intravascular volume depletion, which both may limit the effectiveness of tolvaptan. 45 No predictive value was proposed by the existing evidence for baseline urine osmolality or 24-h urine sodium excretion. However, because tolvaptan exerts its action by binding to V 2 receptors and inhibiting the reabsorption of free water, urine osmolality 4 h after its administration has been reported to be significantly lower in tolvaptan responders.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies [19][20][21][22][23][24][25][26][27] were included in the analysis, with a total of 736 patients. Among them, 451 patients presented clinical response to tolvaptan therapy, while the rest 285 were judged as nonresponders.…”
Section: Included Studiesmentioning
confidence: 99%